Strategi Bimbingan Pranikah sebagai Media Pendidikan dan Pemberdayaan Keluarga di KUA Kecamatan Bungin - Musa Musa; Suparman Suparman; Haerusman Haerusman; Baharuddin Baharuddin; Uli Nuha (LPPM Institut Pendidikan Nusantara Global, 2025)
Premarital guidance is a strategic effort to prepare prospective couples to build a harmonious household. This study was conducted to describe the strategy of premarital guidance as a medium for family education and empowerment at the KUA (Religious Affairs Office) in Bungin District. The purpose of this study was to identify the approaches used in implementing premarital guidance and its effectiveness in improving emotional, spiritual, and social readiness. This study used a descriptive qualitative approach with a field study type. Informants were selected purposively and consisted of the head of the KUA, religious instructors, and prospective couples. The research instrument was the researcher herself, supported by interview guidelines, observation sheets, and documentation. Data collection techniques included in-depth interviews, participatory observation, and document study. Data analysis was conducted using the interactive model of Miles and Huberman, while data validity was obtained through triangulation of sources and techniques. The results of the study indicate that the strategy used is participatory, refers to the principles of andragogy, and integrates local cultural values. This guidance plays an important role in non-formal education that can empower families, although it still requires institutional strengthening and an evaluation system.